The influence of angioarchitectural features on the success of endovascular embolization of cranial dural arteriovenous fistulas with Onyx - Vollherbst, Dominik; Herweh, Christian; Schönenberger, Silvia; Seker, Fatih; Nagel, Simon; Ringleb, Peter A.; Bendszus, Martin; Möhlenbruch, Markus Alfred (American journal of neuroradiology, 2019)
BACKGROUND AND PURPOSE: Endovascular embolization can be an effective treatment for cranial dural arteriovenous fistulas. However, a considerable number of dural arteriovenous fistulas still cannot be treated sufficiently. The purpose of this study was to report our single-center experience of endovascular embolization of dural arteriovenous fistulas with Onyx, including the investigation of the influence of angioarchitectural features on the treatment success. - MATERIALS AND METHODS: Clinical data, angioarchitectural features, complications, treatment success (defined as complete symptom remission for low-grade dural arteriovenous fistulas and complete occlusion for high-grade dural arteriovenous fistulas), and occlusion rates were assessed. The influence of various angioarchitectural features (including location, pattern of venous drainage, and quantity and origin of feeding arteries) was investigated using multivariable backward logistic regression. - RESULTS: One hundred four patients with 110 dural arteriovenous fistulas were treated in 132 treatment procedures. Treatment success and complete occlusion rates were 81.8% and 90.9%, respectively. After a mean follow-up of 23.6 months, 95.5% of the patients showed complete symptom remission or symptom relief. The overall complication rate was 8.3% (4.5% asymptomatic, 2.3% transient, and 1.5% permanent complications). Logistic regression showed that ≥10 feeding arteries (P = .041) and involvement of the ascending pharyngeal artery (P = .039) significantly lowered the probability of treatment success. Treatment success tended to be lower for low-grade dural arteriovenous fistulas, Cognard type I dural arteriovenous fistulas, and dural arteriovenous fistulas with involvement of dural branches of the internal carotid artery, however without reaching statistical significance in the multivariable model. - CONCLUSIONS: The presence of multiple feeding arteries and involvement of the pharyngeal artery negatively influence the treatment success of endovascular embolization of cranial dural arteriovenous fistulas with Onyx.
Gesehen am 21.01.2020